1971
DOI: 10.1070/rc1971v040n07abeh001944
|View full text |Cite
|
Sign up to set email alerts
|

Thermochemical Constants of AIIIBVCompound Semiconductors, and Approximate Methods of Calculation

Abstract: TEA COz laser induced perturbation of shape and intensity of the first Balmer lines emitted by a hydrogen low-pressure glow discharge is investigated for radiation intensity fL in the 10 MW cm-' range. Because of the AC Stark effect, shifts of levels n, = 4, 5, 6, 7 and 8 are measured (i.e. for f~ = 8 MW cm-', AE5 = -0.59 cm-', AEd = 1.81 cm-l, AE7 = 0.55 cm-I). In addition, splitting and optical satellites originating from high orbital quantum numbers are clearly observed on the Ha line. The laser one-and two… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

1971
1971
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…This follows from the fact that AFf~ of GaP is more negative than ~Ff~ of GaAs (7,11,12), and consequently, in this temperature range, the free energy change of Reaction [3] is more negative when GaP is deposited. If thermodynamics were the only factor governing the deposition process, the phosphorus species should have exhibited larger reactivity, since at 700~ GaP should be more readily deposited than GaAs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This follows from the fact that AFf~ of GaP is more negative than ~Ff~ of GaAs (7,11,12), and consequently, in this temperature range, the free energy change of Reaction [3] is more negative when GaP is deposited. If thermodynamics were the only factor governing the deposition process, the phosphorus species should have exhibited larger reactivity, since at 700~ GaP should be more readily deposited than GaAs.…”
Section: Discussionmentioning
confidence: 99%
“…If thermodynamics were the only factor governing the deposition process, the phosphorus species should have exhibited larger reactivity, since at 700~ GaP should be more readily deposited than GaAs. This follows from the fact that AFf~ of GaP is more negative than ~Ff~ of GaAs (7,11,12), and consequently, in this temperature range, the free energy change of Reaction [3] is more negative when GaP is deposited.…”
Section: Table II Comparison Of the Observed Partial Pressures With T...mentioning
confidence: 99%
“…As a result, eq 107 is more trustworthy. 38 -103 Kischio 96 -106 Gardner 89 -235 Gal'chenko et al 37,88 -82 Stone et al 134 -71 Thevenot 87 -464 Zahreeruddin 47 -239 Kubaschewski et al 121 -98 Barin et al 4 -63 45 -109 Kischio 90 -109 Peviak and Sandulova 95 -168 Martusodirdjo and Pratt 40 -61 Zaheeruddin 47 -109 Panish et al 117 -133 De Maria et al 250 -100 McAlister 244 -98 Kubaschewski et al 121 -147 Barin et al 4 -148 Terpiłwski et al 8 -123 Marina and Nashel'skii 251 -104…”
Section: Group Iiiamentioning
confidence: 99%
“…Dew-point methods have also been used on an occasional basis, particularly by Nashel'skii and co-workers. ,− The choice of this technique for experiments with phosphides is dubious, for two reasons. First is the uncertainty over the form of phosphorus which actually condenses; Marina et al reported that the white phosphorus which initially appeared in their experiments quickly changed to “red” . As a result, the assumption of equilibrium, which dew-point measurements require, cannot be made.…”
Section: Gibbs Energiesmentioning
confidence: 99%
“…The lattice mismatch between III-Sb compound materials and Si is quite large with more than 12%. In addition, antimonides are very soft [15,16] and have a reduced activation energy to form misfit defects in comparison to III-V-arsenides and -phosphides, as the III-Sb bond energy is lower [17,18]. All this promotes the formation of 90 • misfit dislocations to release the mismatch strain.…”
Section: Introductionmentioning
confidence: 99%